2016
DOI: 10.1007/s13389-016-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

PAC learning of arbiter PUFs

Abstract: The general concept of physically unclonable functions (PUFs) has been nowadays widely accepted and adopted to meet the requirements of secure identification and key generation/storage for cryptographic ciphers. However, shattered by different attacks, e.g., modeling attacks, it has been proved that the promised security features of arbiter PUFs, including unclonability and unpredictability, are not supported unconditionally. However, so far the success of existing modeling attacks relies on pure trial and err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
(56 reference statements)
0
25
0
Order By: Relevance
“…In particular, the path that dominates the timing for cases where paths reconverge and have nearly equal nominal delays will be different from chip-to-chip. Third, ML algorithms such as Probably Approximately Correct (PAC) that have been effective against arbiter PUFs, guarantee success only when the model is polynomial in size [5,35,36]. Our preliminary work on the physical model indicate that the model has components that appear to be exponential in size, eliminating the possibility of a "guaranteed" success.…”
Section: Security Analysismentioning
confidence: 97%
“…In particular, the path that dominates the timing for cases where paths reconverge and have nearly equal nominal delays will be different from chip-to-chip. Third, ML algorithms such as Probably Approximately Correct (PAC) that have been effective against arbiter PUFs, guarantee success only when the model is polynomial in size [5,35,36]. Our preliminary work on the physical model indicate that the model has components that appear to be exponential in size, eliminating the possibility of a "guaranteed" success.…”
Section: Security Analysismentioning
confidence: 97%
“…Modeling attacks require a subset of CRPs to create a model on that and predict the PUF responses for all possible challenges [41]. It has been reported that an Arbiter PUF under the Deterministic Finite Automata (DFA) representation can be Probably Approximately Correct (PAC) learned with a given level of accuracy and confidence [26].…”
Section: Related Workmentioning
confidence: 99%
“…Here we elaborate briefly on an example of how the LFI can be combined with a well-established ML framework to break the security of an XOR Arbiter PUF. If the attacker could access the response of each individual Arbiter PUF in an XOR Arbiter PUF, each chain can be modeled separately in polynomial time, e.g., following the procedure in [26]. By obtaining a model of the challenge-response behavior of each Arbiter PUF individually, the challenge-response of an XOR Arbiter PUF can be predicted, and hence, the security of the XOR Arbiter PUF is broken.…”
Section: Lfi Attack Against Xor Arbiter Pufsmentioning
confidence: 99%
See 2 more Smart Citations